A Comparative Study on Social Policy Reforms for Facing the Ageing Population in Japan and Italy - Shandika Putra Damayana (Jurnal Jamsostek, 2023)
This study is conducted to analyze the social policies taken from two different countries—Japan and Italy—on facing the issue  of an ageing population. Japan and Italy are chosen as the subjects of this study because both countries have similar demography and socio-economic backgrounds. This study focused on analyzing the policy approach on tackling the ageing population issues, especially related to the birth rate, economy, and labour force. The purpose of this study is to identify and  compare the effectiveness of these social policies taken in both countries. This study is based on desktop research, mostly uses a secondary data analysis approach through online publications, reports, and regulations from the government and related organizations. The result of this study implies that both Japan and Italy have been successful in reducing the impacts of an ageing population. Both countries have similar policies approach related to these issues, such as the economic support for a family with children, work-life balance policies for career parents, and retirement age adjustment. However, related to migration policy, Japan is more restricted than Italy. The Japanese government has a preference to expand its international investments, rather than increasing the migrant entrance. Based on the lessons learned from Japan and Italy, I propose several recommendations for Indonesia.